2017
DOI: 10.1002/slct.201702164
|View full text |Cite
|
Sign up to set email alerts
|

3DOM SiO2-Supported Different Alkali Metals-Modified MnOx Catalysts: Preparation and Catalytic Performance for Soot combustion

Abstract: A series of novel and cheap catalysts, which contain three‐dimensionally ordered macroporous (3DOM) structure and alkali‐doped MnOx nanoparticles, were designed and prepared by a facile method. The physical and chemical properties of as‐prepared catalysts were characterized by XRD, SEM, TEM, Raman and H2‐TPR and so on. The as‐prepared catalysts exhibit excellent catalytic performance for soot combustion, which the T10, T50 and T90 are 275 oC, 323 oC and 351 oC, respectively. This activity result is comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As shown in the Figure 4b-e, the reduction peaks can be divided into four ranges of 178-250 • C, 280-350 • C, 350-450 • C, and >650 • C. Due to the large negative reduction potential, MnO was not reduced to Mn 0 , even above 950 • C. Therefore, MnO was considered to be the final state for the preparation of catalyst reduction [47,48]. According to the reduction process of Mn-based oxides, the first peak at 178-250 • C may be attributed to MnO 2 reduction to Mn 2 O 3 , the second peak at 280-350 • C could be related to Mn 2 O 3 reduction to Mn 3 O 4 , and the third peak at 350-450 • C could belong to the Mn 3 O 4 reduction to MnO [16,49]. The fourth peak at >650 • C is assigned to the reduction of CeO 2 to Ce 2 O 3 .…”
Section: H 2 -Tpr Profiles Of the Prepared Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in the Figure 4b-e, the reduction peaks can be divided into four ranges of 178-250 • C, 280-350 • C, 350-450 • C, and >650 • C. Due to the large negative reduction potential, MnO was not reduced to Mn 0 , even above 950 • C. Therefore, MnO was considered to be the final state for the preparation of catalyst reduction [47,48]. According to the reduction process of Mn-based oxides, the first peak at 178-250 • C may be attributed to MnO 2 reduction to Mn 2 O 3 , the second peak at 280-350 • C could be related to Mn 2 O 3 reduction to Mn 3 O 4 , and the third peak at 350-450 • C could belong to the Mn 3 O 4 reduction to MnO [16,49]. The fourth peak at >650 • C is assigned to the reduction of CeO 2 to Ce 2 O 3 .…”
Section: H 2 -Tpr Profiles Of the Prepared Catalystsmentioning
confidence: 99%
“…Therefore, M was considered to be the final state for the preparation of catalyst reduction [47,48]. cording to the reduction process of Mn-based oxides, the first peak at 178-250 °C ma attributed to MnO2 reduction to Mn2O3, the second peak at 280-350 °C could be relate Mn2O3 reduction to Mn3O4, and the third peak at 350-450 °C could belong to the M reduction to MnO [16,49]. The fourth peak at >650 °C is assigned to the reduction of C to Ce2O3.…”
Section: H 2 -Tpr Profiles Of the Prepared Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…26–28 Alkali metals, potassium in particular, have been investigated intensively as active components for soot combustion. 28–31 Feng et al revealed that as a good electron donor, K + cations are conducive to the adsorption and dissociation of gaseous O 2 on perovskite surfaces. For instance, the presence of K + can weaken the Fe–O or Mn–O bonds on the catalyst surface, thus some of the lattice O 2− will be converted into adsorbed active oxygen anions, which play an important role in accelerating the soot combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, searching for low-cost catalytic materials that may successfully operate below 300–400 °C is currently one of the main challenges for development of efficient and durable catalytic particle filters (CDPF), which are based on earth-abundant components. Although owing to their superior activity, supported highly dispersed platinum group metals have dominated the automotive deSoot catalysis, their high cost and limited availability have triggered a continuous search for alternative cheaper materials. , Among many examined transition metal oxide systems such as spinels and perovskites or ceria-based materials, often functionalized by addition of alkali (K, Na, Li, Rb, and Cs) or f-type metals (La and Pr), mixed oxide systems (Bi 2 O 3 –Fe 2 O 3 , Cu/BaO/La 2 O 3 , CuO/SiO 2 , or Fe 2 O 3 /SiO 2 , along with manganese (Mn 2 O 3 ) and potassium manganese oxides of layered (birnessite, OL) and tunnel (cryptomelane, OMS-2) structures , ) exhibit promising performance as soot oxidation catalysts. Activity of the latter materials may further be improved upon doping with V, Nb, or Fe, which affects the physical and chemical properties of the cryptomelane matrix, the shape of crystallites, and the redox state of Mn, while maintaining the parent OMS-2 molecular architecture.…”
Section: Introductionmentioning
confidence: 99%